An evaluation of cetuximab dosing strategies using pharmacokinetics and cost analysis. (24th May 2019) - Ogungbenro, Kayode; Patel, Alkesh; Saunders, Mark; Clark, James; Duncombe, Robert
Abstract: Objectives: Cetuximab dosing is based on body surface area (BSA), an approach that is associated with significant wastage due to available vial sizes. NHS England recently introduced an alternative strategy for cetuximab dosing based on dose banding. The aim of this work was to investigate approaches to cetuximab dosing to improve its cost-effectiveness. Methods: A simulation study using a population pharmacokinetic model was used to assess the performance of dosing strategies using exposure, probability of target attainment and cost. Two dosage regimens (500 and 400/250 mg/m 2 ) were investigated; 5% and 10% dose banding, fixed and optimised dosing strategies were evaluated and compared to BSA strategy. Key findings: The percentage of the total cost associated with wastage for the 400/250 mg/m 2 regimen were 8.75%, 5.13%, 3.61%, 9.2% and 0% for BSA; 5 and 10% bands; fixed and optimal strategies, respectively. Similar results were obtained for 500 mg/m 2 regimen. In comparison with BSA strategy, other strategies have comparable or improved performance. Optimised strategy showed consistent performance and ensures equal exposure and probability of target attainment. Conclusions: Cost-effectiveness of cetuximab treatment can be improved with alternative strategies by reducing wastage without compromising exposure.